Case report: ATIC-ALK fusion in infant-type hemispheric glioma and response to lorlatinib - Shahab, Shubin W.; Schniederjan, Matthew; Vega, Jose Velazquez; Little, Stephen; Reisner, Andrew; MacDonald, Tobey; Aguilera, Dolly (Frontiers in Oncology, 2023)
Introduction: Infant type hemispheric gliomas are a rare tumor with unique molecular characteristics. In many cases these harbor mutations in receptor tyrosine kinase pathways and respond to targeted therapy. Here we describe the case of an infant with this type of tumor with a novel ATIC-ALK fusion that has responded dramatically to the ALK inhibitor lorlatinib, despite being refractory to standard chemotherapy. Case Description The infant was initially treated with standard chemotherapy and found to have an ATIC-ALK fusion. When surveillance imaging revealed progressive disease, the patient was switched to the ALK-inhibitor lorlatinib at 47 mg/m2/day. The patient demonstrated a significant clinical and radiographic response to the ALK inhibitor lorlatinib after just 3 months of treatment and a near complete response by 6 months of therapy. Conclusion: The ALK inhibitor lorlatinib is an effective targeted therapy in infant type hemispheric glioma patients harboring ATIC-ALK fusion.